Sakinah Family Concept of Career Spouses at Pesantren Darul Ulum Rejoso Peterongan Jombang - Hikmah, Ilmiani Nurul; Zaenul Mahmudi, Zaenul Mahmudi (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Islam has regulated the concept of marriage in great detail based on the texts of the Qur'an and Hadith so that human life is organized and the purpose of marriage itself is achieved. Marriage is something that has been required in the Islam teachings, especially for those who are physically and mentally capable. One of the goals of marriage is to build a sakinah household, which can be an ark and a captain for His heaven. In the 1945 Constitution, it is stated that every community has the right to marry, form a happy family, and carry on offspring with a legal marriage. This study is an empirical research that use a qualitative approach, the data sources used are primary and secondary data source. The primary data source is the interview result conducted with married spouses who work career also as caregiver in the Pesantren foundation, especially at Pesantren Darul Ulum Rejoso Peterongan Jombang. Secondary data source in the form of texts or nash of the qur'an and hadith and also some other literature such as laws that specifically regulate marriage, family and problems in it, papers, thesis, and thesis from previous research which also discusses about sakinah family, career family, and everything related to it. The result study conclude that some efforts carried out or implemented by several husband and wife career worker as Pesantren caregivers in Pesantren Darul Ulum Jombang include an even distribution of household tasks, good time management, families who apply a sense of mutual understanding, appreciate and respect, so that there are no friction problems in the family, husband and wife who understand each other's rights and obligation, animate a religious atmosphere. Then, the category or level of the Sakinah family, occupy the Sakinah Family Level III Plus, namely family that have been able to fulfill all the needs of faith, piety and good morals perfectly, psychological social needs, and development and can become role model for the social community environment.